Software Engineering Methods in Systems and Network Systems Proceedings of 7th Computational Methods in Systems and Software 2023, Vol. 1 - Silhavy, Radek; Silhavy, Petr (Lecture Notes in Networks and Systems, 2024)
XV, 463 p. 220 illus., 157 illus. in color.